Cu-Ni-Si copper alloy sheet, plated Cu-Ni-Si copper alloy sheet and manufacturing method thereof
The Cu-Ni-Si copper alloy sheet with a controlled Ni concentration gradient and limited surface Ni concentration addresses the issue of poor electrical connection reliability and solder wettability in high-temperature environments by suppressing Ni diffusion and oxidation, ensuring reliable plating film adhesion and reduced contact resistance.
Patent Information
- Application Number
- JP2020049473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-03-19
AI Technical Summary
Conventional Cu-Ni-Si copper alloy sheets exhibit poor electrical connection reliability, high contact resistance, and reduced solder wettability in high-temperature environments due to Ni oxidation and diffusion, leading to plating film peeling.
A Cu-Ni-Si copper alloy sheet with controlled Ni concentration gradient in the thickness direction, where the surface Ni concentration is 70% or less of the bulk Ni concentration, and a plating film formed with a specific Ni concentration of 10% or less, suppressing Ni diffusion and oxidation.
The solution enhances electrical connection reliability, improves solder wettability, and prevents plating film peeling in high-temperature environments by reducing contact resistance and maintaining mechanical properties.
Smart Images

Figure 0007604778000012 
Figure 0007604778000013 
Figure 0007604778000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a Cu-Ni-Si-based copper alloy sheet containing Ni and Si, a Cu-Ni-Si-based copper alloy sheet having a plating film obtained by plating the copper alloy sheet, and a method for producing the same. [Background technology]
[0002] In recent years, with the progress of miniaturization, thinning, and weight reduction of electronic devices such as mobile terminals, terminals and connector parts used in these devices are also becoming smaller and have narrower electrode pitches. Electronic devices used around automobile engines are required to be reliable under high temperature and severe conditions. Accordingly, in order to maintain the reliability of the electrical connections, further improvements in strength, conductivity, spring limit value, stress relaxation characteristics, bending workability, fatigue resistance, etc. are required, and Cu-Ni-Si-based copper alloy sheets containing Ni and Si shown in Patent Documents 1 to 3 are used.
[0003] Patent Document 1 discloses a Cu alloy for electric and electronic components having a composition containing, by mass%, 0.5-3% Ni, 0.1-0.9% Sn, 0.08-0.8% Si, 0.1-3% Zn, 0.007-0.25% Fe, 0.001-0.2% P, 0.001-0.2% Mg, and the remainder being Cu and unavoidable impurities.
[0004] Patent Document 2 describes a copper alloy plate containing 1.0 to 4.0 mass% Ni, 0.2 to 0.9 mass% Si, 0.3 to 1.5 mass% Zn, 0.001 to 0.2 mass% P, with the remainder being Cu and unavoidable impurities, as a base material, which has a plating film layer consisting of a surface Sn phase having a thickness of 0.2 μm or less, a Sn phase having a thickness of 0.2 to 0.8 μm, a Sn-Cu alloy phase having a thickness of 0.5 to 1.4 μm, and a Cu phase having a thickness of 0 to 0.8 μm, in this order, from the surface to the base material. The present invention discloses a Cu-Ni-Si based copper alloy Sn-plated sheet, characterized in that the ratio (C / D) of the P concentration (C) of the surface Sn phase to the P concentration (D) of the base material is 1.1 to 2.0, and the ratio (A / B) of the Zn concentration (A) in the boundary layer having a thickness of 0.8 to 1.4 μm between the plating film layer and the base material to the Zn concentration (B) of the base material is 0.5 to 0.8, thereby achieving a high level of balance between plating heat peel resistance and contact electrical resistance, and a method for producing the same.
[0005] Patent Document 3 discloses a Cu-Ni-Si copper alloy sheet material for Sn plating having excellent heat resistance and reliability, which contains 1.0 to 4.0 mass% Ni, 0.2 to 0.9 mass% Si, and 0.7 to 2.0 mass% Zn, with the balance being Cu and unavoidable impurities, and is characterized in that in the Cu-Ni-Si copper alloy sheet material that has been subjected to solution treatment and aging treatment accompanied by recrystallization, the metal Zn concentration at a depth of 0.2 μm from the surface is 0.7 mass% or more as measured by Auger electron spectroscopy. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-145847 [Patent Document 2] JP 2014-005481 A [Patent Document 3] JP 2010-111926 A Summary of the Invention [Problem to be solved by the invention]
[0007] Many conventional Cu-Ni-Si copper alloy sheets have been invented that are excellent in strength, bending workability, electrical conductivity, stress relaxation resistance, etc., but with the electrification of automobiles, sensors have come to be installed around the engine of automobiles or directly on the engine. Terminals and connectors used around the engine of automobiles are increasingly being used in higher temperature environments than ever before, but there were no conventional Cu-Ni-Si copper alloy sheets that showed fully satisfactory properties in terms of contact electrical resistance in high temperature environments.
[0008] In addition, many of the reflow Sn-plated sheets, which are made by applying Sn plating to conventional Cu-Ni-Si-based copper alloys and then performing a heating and melting process (reflow process), have excellent properties such as heat peeling resistance, contact electrical resistance, corrosion resistance, and press workability. However, there have been no Sn-plated sheets after reflow process that have a high level and a good balance of plating heat peeling resistance, contact electrical resistance, and solder wettability under the harsh high-temperature environment conditions that are currently required.
[0009] The present invention has been made in consideration of the above circumstances, and aims to improve the electrical connection reliability in a high-temperature environment in a Cu-Ni-Si-based copper alloy sheet containing Ni and Si, and to improve the electrical connection reliability, solder wettability, and adhesion of a plating film in a high-temperature environment even in a Cu-Ni-Si-based copper alloy sheet with a plating film of Sn or the like. [Means for solving the problem]
[0010] In view of these circumstances, the present inventors conducted extensive research and discovered that the increase in contact electrical resistance (hereinafter also referred to as "contact resistance") in high-temperature environments is caused by the oxidation of Ni present on the surface of the base material, and that in particular, when a base material is plated with Sn and then subjected to a heat melting treatment, Ni diffuses due to heating and reaches the surface of the plating film, resulting in a significant increase in contact resistance and a decrease in solder wettability in high-temperature environments. In this case, the copper alloy base material is alloyed with Sn, so that Ni is taken into the Sn-Cu alloy layer and the Sn layer, making it easier for Ni to diffuse to the surface of the plating film.
[0011] In addition, because Ni is an active element, the Ni on the surface of the copper alloy sheet before plating immediately turns into Ni oxide. When plating a copper alloy sheet with a high Ni content on the surface, the Ni oxide on the base material surface cannot form a metallic bond with the metal in the plating film, resulting in poor adhesion of the plating film and making it prone to peeling in high-temperature environments.
[0012] Based on such knowledge, the present invention aims to appropriately control the Ni concentration in the surface layer of the copper alloy sheet, thereby suppressing the oxidation of the surface of the copper alloy sheet and suppressing an increase in contact electrical resistance in a high-temperature environment, and to reduce the Ni concentration in the plating film even if a plating film is formed, thereby suppressing an increase in contact resistance in a high-temperature environment, and improving solder wettability and adhesion.
[0013] The Cu-Ni-Si based copper alloy sheet of the present invention is a copper alloy sheet containing, at the center portion in the thickness direction of the sheet, 0.4 mass% or more and 5.0 mass% or less of Ni and 0.05 mass% or more and 1.2 mass% or less of Si, with the remainder being Cu and unavoidable impurities, wherein the surface Ni concentration at the sheet surface is 70% or less of the Ni concentration (hereinafter referred to as "bulk Ni concentration") at the center portion in the thickness direction (hereinafter also referred to as "bulk"), and in a surface layer portion at a depth from the sheet surface to a depth where the Ni concentration is 90% of the bulk Ni concentration, the Ni concentration increases with a concentration gradient of 5 mass% / μm or more and 100 mass% / μm or less from the sheet surface toward the center portion in the thickness direction.
[0014] In other words, the Cu-Ni-Si based copper alloy sheet of the present invention has a surface layer portion having a gradient of Ni concentration from the sheet surface in the sheet thickness direction, and an interior portion including a thickness center portion where the Ni concentration is approximately uniform, and the components in the thickness center portion are Ni: 0.4 mass% to 5.0 mass%, Si: 0.05 mass% to 1.2 mass%, and the balance: Cu and unavoidable impurities, and the surface Ni concentration at the sheet surface is 0% to 70% of the bulk Ni concentration at the thickness center portion, and the Ni concentration in the surface layer portion increases from the sheet surface toward the thickness center portion with a concentration gradient of 5 mass% / μm to 100 mass% / μm, and is highest in the deepest portion of the surface layer portion, being 90% of the bulk Ni concentration.
[0015] This copper alloy sheet has a surface Ni concentration of 70% or less of the bulk Ni concentration, so Ni oxide is unlikely to form on the sheet surface and has excellent electrical connection reliability, so it can be used as a contact point as is without plating or other treatments. In addition, even if a plating film is subsequently formed and then heat-treated, Ni diffusion into the plating film can be suppressed, which suppresses an increase in contact resistance in a high-temperature environment, provides excellent solder wettability, and prevents peeling of the plating film.
[0016] From the viewpoint of preventing oxidation of the sheet surface and suppressing Ni diffusion into the plating film, the surface Ni concentration is preferably 70% or less of the bulk Ni concentration. In addition, the surface layer where the Ni concentration gradient changes sharply is thin, in other words, the thickness of the surface layer having the Ni concentration gradient is appropriate, so that Ni diffusion is suppressed while the excellent mechanical properties of the copper alloy are maintained.
[0017] In the surface layer, if the Ni concentration gradient from the sheet surface is less than 5 mass% / μm, the property of suppressing Ni diffusion into the plating film is saturated, but the surface layer with a low Ni concentration is thick and the desired Ni concentration is not achieved until a considerable depth is reached, impairing the properties of the Ni-containing copper alloy sheet. On the other hand, if the Ni concentration gradient exceeds 100 mass% / μm, the surface layer with a low Ni concentration becomes too thin compared to the center of the thickness, and the effect of suppressing Ni diffusion is poor.
[0018] In one embodiment of the Cu-Ni-Si-based copper alloy sheet according to the present invention, the thickness of the surface layer is 0.8 μm or less. If the thickness of the surface layer exceeds 0.8 μm, the proportion of the range with a low Ni content in the entire sheet thickness increases, and there is a risk of impairing the mechanical properties of the Ni-containing copper alloy. This deterioration of properties is particularly noticeable when the sheet thickness is thin.
[0019] The plated Cu-Ni-Si-based copper alloy sheet of the present invention comprises a plated film formed on the surface layer portion of the copper alloy sheet.
[0020] This copper alloy sheet with a plating film has a low Ni concentration on the surface of the copper alloy sheet, and therefore has little Ni oxide, resulting in excellent adhesion of the plating film. In addition, the amount of Ni diffusing into the plating film can be reduced, which suppresses an increase in contact electrical resistance in high-temperature environments and provides excellent solder wettability and heat peeling resistance of the plating.
[0021] In one embodiment of the plated Cu-Ni-Si based copper alloy sheet according to the present invention, the average concentration of Ni in the plated film is 10% or less of the bulk Ni concentration.
[0022] In this plated copper alloy sheet, if the average Ni concentration in the plated film exceeds 10% of the bulk Ni concentration, the effect of surface diffusion of Ni on the contact resistance becomes large.
[0023] In another embodiment of the Cu-Ni-Si-based copper alloy sheet with a plating film according to the present invention, the plating film is made of one or more layers selected from tin, copper, zinc, gold, silver, palladium, and alloys thereof. By using these metals or alloys for the plating film, the copper alloy sheet with a plating film has excellent electrical connection reliability and can be suitably used as a connector terminal.
[0024] The method for producing a Cu-Ni-Si based copper alloy sheet of the present invention includes a Ni enrichment treatment in which Ni in a Ni-containing copper alloy sheet is diffused toward a surface of the Ni-containing copper alloy sheet to generate a Ni concentration gradient in the sheet thickness direction and form a Ni-enriched portion in which Ni is enriched, and a surface portion removal treatment in which the Ni-enriched portion in which Ni is enriched is removed to form the surface layer portion.
[0025] With this manufacturing method, the surface layer formed by removing the Ni-enriched areas has a lower Ni concentration than the center of the plate, which reduces the generation of an oxide film on the plate surface and suppresses the increase in contact electrical resistance in high-temperature environments.
[0026] The method for producing a Cu-Ni-Si-based copper alloy sheet having a plating film of the present invention comprises: applying the plating film at a current density of 0.1 A / dm 2 More than 60A / dm 2 The following electrolytic plating process is used. The current density during electrolytic plating is 0.1 A / dm 2 If the current density is less than 60 A / dm, the deposition rate is slow and it is not economical. 2 If it exceeds this value, the diffusion limit current density is exceeded, and a film without defects cannot be formed.
[0027] For example, when a tin plating film is formed by electrolytic plating, a reflow treatment may be performed after the electrolytic plating in order to suppress the generation of whiskers. That is, in one embodiment of the method for producing a copper alloy sheet with a plating film according to the present invention, after the electrolytic plating to form the tin-containing plating film, a reflow treatment is performed at a heating peak temperature of 230° C. or more and 330° C. or less, preferably 300° C. or less, and a heating time at the heating peak temperature of 0.5 seconds or more and 30 seconds or less, preferably 1 second or more and 20 seconds or less.
[0028] If the peak heating temperature during reflow treatment is less than 230°C or the heating time is less than 0.5 seconds, the tin will not remelt and the effect of suppressing the generation of whiskers will not be obtained. If the heating temperature exceeds 330°C or the heating time exceeds 30 seconds, excessive heating will cause Ni to diffuse into the plating film surface, increasing contact resistance in a high-temperature environment and decreasing solder wettability. Effect of the Invention
[0029] According to the present invention, it is possible to suppress oxidation of the surface of a Cu-Ni-Si based copper alloy sheet, improve electrical connection reliability, reduce the Ni concentration in a plating film even when a plating film is formed, suppress an increase in contact resistance in a high temperature environment, improve the solder wettability of the plating film surface, and improve the adhesion between the plating film and the Cu-Ni-Si based copper alloy sheet. [Brief description of the drawings]
[0030] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of one embodiment of a Cu-Ni-Si-based copper alloy sheet having a plating layer according to the present invention. [Diagram 2] FIG. 2 is a Ni component analysis diagram in the depth direction of a Cu-Ni-Si-based copper alloy plate measured by XPS. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] An embodiment of the present invention will be described. In the plated Cu-Ni-Si-based copper alloy sheet 1 of this embodiment, a plated film 20 is formed on a sheet surface 10a of a Cu-Ni-Si-based copper alloy sheet (hereinafter simply referred to as a copper alloy sheet) 10 containing Ni and Si, and the plated film 20 is formed by laminating a Cu layer 21, a Sn-Cu alloy layer 22, and a Sn layer 23 in this order (see FIG. 1).
[0032] [Copper alloy plate] The copper alloy sheet 10 contains, at the center portion in the sheet thickness direction, 0.4 mass % to 5.0 mass % Ni, 0.05 mass % to 1.2 mass % Si, and the balance being Cu and unavoidable impurities.
[0033] (Ni, Si) By applying appropriate heat treatment, Ni and Si form fine particles of an intermetallic compound, mainly Ni2Si, which significantly increases the strength of the alloy and at the same time increases its electrical conductivity. Ni is added in the range of 0.4 mass% to 5.0 mass%. If Ni is less than 0.4 mass%, sufficient strength cannot be obtained. If Ni is more than 5.0 mass%, cracks occur during hot rolling. Ni is preferably 0.8 mass% to 4.0 mass%, and more preferably 1.0 mass% to 3.0 mass%. Si is added in the range of 0.05% by mass to 1.2% by mass. If the Si content is less than 0.05% by mass, the strength decreases. If the Si content exceeds 1.2% by mass, not only does it not contribute to the strength, but the electrical conductivity decreases due to the excess Si. Preferably, Si is 0.1% by mass to 1.0% by mass, and more preferably, Si is 0.2% by mass to 0.9% by mass.
[0034] Regarding the Ni content in the copper alloy sheet 10, the Ni concentration at the center of the thickness where the Ni concentration is stable (bulk Ni concentration) is 0.4 mass% or more and 5.0 mass% or less (preferably 1.0 mass% or more and 3.0 mass% or less) as mentioned above, but the Ni concentration at the sheet surface 10a (hereinafter, "surface Ni concentration") is 70% or less (0% or more) of the bulk Ni concentration.
[0035] Since the surface Ni concentration of the copper alloy sheet 10 is 70% or less of the bulk Ni concentration, Ni oxide is unlikely to occur on the sheet surface 10a, and even if plating is subsequently performed and then heat-treated, Ni diffusion into the plating film 20 can be suppressed. Therefore, the solder wettability is excellent, and peeling of the plating film 20 can be prevented.
[0036] From the viewpoint of preventing oxidation of the sheet surface 10a and suppressing Ni diffusion into the plating film 20, it is sufficient that the sheet surface 10a does not contain Ni (the surface Ni concentration is 0% of the bulk Ni concentration), but if the surface Ni concentration is 70% or less of the bulk Ni concentration, the sheet surface 10a is preferably provided with the properties of a Ni-containing copper alloy to some extent. A more preferred surface Ni concentration is 50% or less of the bulk Ni concentration, more preferably 30% or less, and even more preferably 15% or less.
[0037] The Ni content in the copper alloy sheet 10 has a concentration gradient of 5 mass% / μm or more and 100 mass% / μm or less from the sheet surface 10a toward the center of the sheet thickness. The range from the sheet surface 10a to where the Ni concentration becomes 90% of the bulk Ni concentration due to this concentration gradient is defined as the surface layer portion 11.
[0038] If the Ni concentration gradient in the thickness direction of the copper alloy sheet 10 is less than 5 mass% / μm, the desired Ni concentration is not reached until a considerable depth is reached, and the properties of the Ni-containing copper alloy sheet are impaired. On the other hand, if it exceeds 100 mass% / μm, the effect of suppressing Ni diffusion is poor. The Ni concentration gradient is preferably in the range of 5 mass% / μm to 100 mass% / μm, more preferably 10 mass% / μm to 50 mass% / μm, and even more preferably 15 mass% / μm to 40 mass% / μm.
[0039] The surface layer 11 has a thickness of preferably 0.8 μm or less, more preferably 0.5 μm or less, and further preferably 0.2 μm or less. There is no particular lower limit to the thickness, but from the viewpoint of the effects of the present invention, it is preferable to set the thickness to 0.01 μm or more. In the copper alloy sheet 10, the part inside the surface layer 11 is referred to as the sheet interior 12.
[0040] Fig. 2 is a graph showing the results of analyzing the Ni content of the copper alloy sheet 10 in the depth direction. A sample obtained by thinning the copper alloy sheet 10 in the thickness direction was analyzed by an X-ray photomolecular spectroscopy (XPS). In Fig. 2, the horizontal axis shows the depth (distance) from the sheet surface 10a, and the vertical axis shows the XPS spectrum intensity, i.e., the Ni concentration. The arithmetic average of the maximum and minimum values of the Ni concentration at the thickness center where the Ni concentration is stable is defined as the bulk Ni concentration at the center. The thickness of the surface layer 11 is defined as the depth to the position where the Ni concentration, which changes from the sheet surface 10a toward the thickness center, first reaches 90% of the bulk Ni concentration.
[0041] (Co, Sn, Zn) (1) Furthermore, the Cu-Ni-Si based copper alloy sheet of the present invention may contain one or more of 0.1 mass% or more and 1.0 mass% or less of Co, 0.1 mass% or more and 1.0 mass% or less of Sn, and 0.1 mass% or more and 3.0 mass% or less of Zn. Co can replace Ni in the Ni2Si intermetallic compound formed by heat treatment to form an intermetallic compound, improving the strength and electrical conductivity of the alloy. If Co exceeds 1.0 mass%, the precipitates become coarse and the bending workability deteriorates. If Co is less than 0.1 mass%, no improvement in strength is observed. Preferably, Co is 0.2 mass% or more and 0.8 mass% or less. Sn and Zn have the effect of improving strength and heat resistance, and furthermore Sn has the effect of improving stress relaxation resistance, and Zn has the effect of improving heat resistance of solder joints. Sn is added in the range of 0.1 mass% to 1.0 mass%, preferably 0.2 mass% to 0.8 mass%, and Zn is added in the range of 0.1 mass% to 3.0 mass%, preferably 0.2 mass% to 0.8 mass%. Below this range, the desired effect cannot be obtained, and above this range, the conductivity decreases.
[0042] (Mg) (2) Furthermore, the Cu-Ni-Si based copper alloy sheet of the present invention may contain 0.001 mass % or more and 0.2 mass % or less of Mg. Mg has the effect of improving stress relaxation properties and hot workability, but if it is less than 0.001 mass%, there is no effect, and if it exceeds 0.2 mass%, castability (deterioration of casting surface quality), hot workability, and plating heat peeling resistance are deteriorated. Preferably, Mg is 0.01 mass% or more and 0.15 mass% or less.
[0043] (Fe, P, C, Cr, Zr) (3) Furthermore, the Cu-Ni-Si system copper alloy sheet of the present invention may contain, in addition to any one of the components (1) and (2), one or more of the following: 0.007% by mass or more and 0.25% by mass or less of Fe; 0.001% by mass or more and 0.2% by mass or less of P; 0.0001% by mass or more and 0.001% by mass or less of C; 0.001% by mass or more and 0.3% by mass or less of Cr; and 0.001% by mass or more and 0.3% by mass or less of Zr. Fe has the effect of improving hot rolling properties (suppressing the occurrence of surface cracks and edge cracks), refining precipitated compounds of Ni and Si, and improving the adhesion of the plating film in a high-temperature environment, but if the content is less than 0.007 mass%, the desired effect cannot be obtained, while if the content exceeds 0.25 mass%, the effect of improving hot rolling properties is saturated and the electrical conductivity is adversely affected, so the content is set to 0.007 mass% or more and 0.25 mass% or less. Preferably, Fe is 0.01 mass% or more and 0.2 mass% or less. P has the effect of suppressing the loss of springiness caused by bending, but if its content is less than 0.001 mass%, the desired effect cannot be obtained, while if its content exceeds 0.2 mass%, solder heat peeling resistance is impaired, so its content is set to 0.001 mass% or more and 0.2 mass% or less. Preferably, P is 0.005 mass% or more and 0.1 mass% or less. C has the effect of improving press punching workability and further improving the strength of the alloy by refining the intermetallic compound of Ni and Si, but if its content is less than 0.0001 mass%, the desired effect cannot be obtained, while if its content exceeds 0.001 mass%, it adversely affects hot workability, which is not preferable, so its content is set to 0.0001 mass% or more and 0.001 mass% or less. Preferably, C is 0.0001 mass% or more and 0.0008 mass% or less. Cr and Zr have a strong affinity with C, making it easier to include C in the Cu alloy, and also have the effect of further refining the Ni and Si intermetallic compounds to improve the strength of the alloy, and further improving the strength by their own precipitation, but if the content is less than 0.001 mass%, the effect of improving the strength of the alloy cannot be obtained, and if it exceeds 0.3 mass%, large precipitates of Cr and / or Zr are generated, which deteriorates the plating adhesion, deteriorates the press punching workability, and further impairs the hot workability, which is not preferable, so the contents of these elements are set to 0.001 mass% or more and 0.3 mass% or less. Preferably, Cr and Zr are each 0.01 mass% or more and 0.2 mass% or less.
[0044] [Plating film] The plating film 20 is formed on the sheet surface 10a of the copper alloy sheet 10 by, in this order, a Cu layer 21 having a thickness of 0 μm to 1 μm, a Sn—Cu alloy layer 22 having a thickness of 0.1 μm to 1.5 μm, and a Sn layer 23 having a thickness of 0.1 μm to 3.0 μm.
[0045] If the thickness of the Cu layer 21 exceeds 1 μm, the thermal stress generated inside the plating film 20 increases in a high-temperature environment, which may cause peeling of the plating film 20. The Cu layer 21 may not be present.
[0046] The Sn-Cu alloy layer 22 is hard, and if the thickness is less than 0.1 μm, the effect of reducing the insertion force when used as a connector may be weakened, resulting in a risk of reduced strength. If the thickness exceeds 1.5 μm, the thermal stress generated in the plating film 20 in a high-temperature environment may become high, resulting in a risk of peeling off of the plating film 20.
[0047] If the thickness of the Sn layer 23 is less than 0.1 μm, the solder wettability may decrease, and if the thickness exceeds 3.0 μm, the thermal stress generated inside the plating film 20 in a high-temperature environment may become high.
[0048] The Ni concentration in the plating film 20 having the above-mentioned layer configuration is 10% or less (0% or more) of the bulk Ni concentration of the copper alloy sheet 10.
[0049] If the average concentration of Ni in the plating film 20 exceeds 10% of the bulk Ni concentration of the copper alloy sheet 10, Ni in the plating film may diffuse to the plating film surface 20a, reducing the solder wettability. The average concentration of Ni in the plating film 20 is more preferably 5% or less of the Ni concentration at the center of the copper alloy sheet 10, and even more preferably 3% or less.
[0050] [Manufacturing method] A method for producing the Cu-Ni-Si based copper alloy sheet 1 having a plating film configured as above will be described.
[0051] The plated Cu-Ni-Si-based copper alloy sheet 1 is produced by producing a copper alloy mother sheet having a composition containing 0.4 to 5.0 mass % Ni, 0.05 to 1.2 mass % Si, with the remainder being Cu and unavoidable impurities (copper alloy mother sheet production process), subjecting this copper alloy mother sheet to a surface treatment to produce a copper alloy sheet (surface treatment process), and then plating (plating process) and reflow treatment (reflow treatment process).
[0052] (Copper alloy mother plate manufacturing process) The copper alloy mother plate is manufactured by melting and casting a material having a composition within the above range to produce a copper alloy ingot, and then subjecting the copper alloy ingot to a process including hot rolling, cold rolling, solution treatment, aging annealing, and finish cold rolling in this order. In this embodiment, the thickness of the copper alloy mother plate is 0.2 mm.
[0053] (Surface treatment process) The obtained copper alloy mother plate is subjected to a surface treatment, which includes a Ni enrichment treatment in which Ni in the copper alloy mother plate is diffused toward the surface of the copper alloy mother plate to generate a Ni concentration gradient in the plate thickness direction and enrich Ni in the surface portion of the copper alloy mother plate to form a Ni enriched portion, and a surface portion removal treatment in which the Ni enriched portion is removed.
[0054] In the Ni enrichment treatment, the copper alloy mother plate is heated to a predetermined temperature for a predetermined time in an oxidizing atmosphere such as oxygen or ozone. In this case, the heating temperature is 100°C or higher, and the heating time is within a time period in which recrystallization does not occur, and the heat treatment may be performed at any temperature taking into consideration equipment restrictions and economic efficiency. For example, the heating time may be long at low temperatures and short at high temperatures, such as 1 minute at 350°C, 2 hours at 300°C, or 5 hours at 250°C.
[0055] The oxidizing substance concentration in the oxidizing atmosphere may be, for example, 5 to 4000 ppm in the case of ozone, preferably 10 to 2000 ppm, and more preferably 20 to 1000 ppm. When oxygen is used without ozone, the atmospheric concentration is preferably at least twice as high as that when only ozone is used. An oxidizing substance such as ozone may be mixed with oxygen. Before the Ni enrichment treatment, a treatment for promoting Ni diffusion, such as introduction of strain or vacancies by mechanical polishing, may be performed.
[0056] As the surface removal treatment, chemical polishing, electrolytic polishing, mechanical polishing, etc. can be performed alone or in combination with a plurality of them on the copper alloy mother plate that has been subjected to Ni enrichment treatment.
[0057] The chemical polishing can be performed by selective etching, etc. The selective etching can be performed by etching using an acidic or alkaline liquid containing a component capable of suppressing copper corrosion, such as a nonionic surfactant, a heterocyclic compound having a carbonyl group or a carboxyl group, an imidazole compound, a triazole compound, or a tetrazole compound.
[0058] Electrolytic polishing can be carried out, for example, by using an acid or alkaline liquid as an electrolyte and by electrolysis of components that tend to segregate at the grain boundaries of copper, thereby preferentially etching the grain boundaries.
[0059] Mechanical polishing can be performed using various commonly used methods such as blasting, lapping, polishing, buffing, grinder polishing, and sandpaper polishing.
[0060] In this way, the copper alloy mother plate is subjected to Ni enrichment treatment and surface portion removal treatment to form the copper alloy plate 10. That is, in the copper alloy plate 10, as described above, the Ni concentration in the surface layer portion 11 is lower than the Ni concentration in the thickness center portion, and the Ni concentration increases with a predetermined concentration gradient from the plate surface 10a toward the center in the plate thickness direction. The bulk Ni concentration in the copper alloy plate 10 is approximately equal to the Ni concentration (bulk Ni concentration) in the thickness center portion of the copper alloy mother plate.
[0061] (Plating process) Next, a plating process is performed to form a plating film 20 on the sheet surface 10a of the copper alloy sheet 10. After removing dirt and natural oxide films by degreasing, pickling, etc., the sheet surface 10a of the copper alloy sheet 10 is subjected to a Cu plating process to form a Cu plating layer thereon, and then a Sn plating process is performed on the surface of the Cu plating layer to form a Sn plating layer.
[0062] The Cu plating layer and the Sn plating layer are preferably pure copper and pure tin plating layers, respectively, but may be Cu alloy plating layers and Sn alloy plating layers containing other elements, respectively, as long as the effects of the present invention are not impaired.
[0063] Each plating layer is plated with a current density of 0.1A / dm 2 More than 60A / dm 2 The plating is performed using the following electrolytic plating method. The current density during electrolytic plating is 0.1A / dm 2 If the current density is less than 60 A / dm, the deposition rate is slow and it is not economical. 2 If it exceeds this value, the diffusion limit current density is exceeded, and a film without defects cannot be formed.
[0064] Table 1 shows an example of the Cu or Cu alloy plating conditions, and Table 2 shows an example of the Sn or Sn alloy plating conditions.
[0065] [Table 1]
[0066] [Table 2]
[0067] (Reflow processing process) Next, the copper alloy sheet 10 on which these plating layers are formed is subjected to a reflow treatment in which the peak heating temperature is set to 230°C or more and 330°C or less, the peak heating temperature is held for 0.5 seconds or more and 30 seconds or less, and then the temperature is cooled to 60°C or less.
[0068] By carrying out the reflow treatment, a plating film 20 consisting of a Cu layer 21 having a thickness of 0 μm to 1 μm, a Sn-Cu alloy layer 22 having a thickness of 0.1 μm to 1.5 μm, and a Sn layer 23 having a thickness of 0.1 μm to 3.0 μm is formed in this order on the sheet surface 10a of the copper alloy sheet 10. Note that in this reflow treatment, all of the Cu in the Cu plating layer may be alloyed with the Sn in the Sn plating layer, and the Cu layer 21 may not be formed.
[0069] This reflow treatment not only causes some Cu in the sheet surface 10a of the copper alloy sheet 10 to diffuse into the plating film 20 and alloy with Sn constituting the plating film 20 to form the Sn-Cu alloy layer 22, but also causes Ni in the sheet surface 10a to diffuse into the plating film 20 and be incorporated into the Sn-Cu alloy layer 22 and the Sn layer 23. However, since the Ni concentration in the sheet surface 10a of the copper alloy sheet 10 is made low, the amount of Ni incorporated into the plating film 20 is small, and the diffusion of Ni into the plating film surface 20a can be effectively suppressed.
[0070] In addition, since the sheet surface 10a of the copper alloy sheet 10 contains very little Ni, there is also little surface oxide, and even if a small amount of oxide is present, it can be easily removed by normal cleaning or the like before plating. Therefore, this copper alloy sheet 1 with a plating film also has excellent adhesion between the plating film 20 and the copper alloy sheet 10. And, since Ni oxide is unlikely to occur on the plating film surface 20a, the copper alloy sheet 1 with a plating film also has excellent solder wettability.
[0071] In the above embodiment, the plating film 20 consisting of the Cu layer 21, the Sn-Cu alloy layer 22, and the Sn layer 23 in this order is formed on the copper alloy sheet 10. However, the plating film is not limited to this and may be composed of one or more layers selected from tin, copper, zinc, gold, silver, palladium, and alloys thereof. EXAMPLES
[0072] [Example 1] Ingots of copper alloys having the compositions shown in Table 3 were prepared, and were subjected to hot rolling, intermediate rolling, solution treatment, aging annealing, cold rolling, etc. in a conventional manner to produce copper alloy mother sheets.
[0073] Next, each copper alloy mother plate was subjected to Ni concentration treatment by heating under various conditions in an oxidizing atmosphere at a heating temperature of 300 to 600°C for a heating time of 1 minute to 5 hours, and then subjected to a surface removal treatment to produce each copper alloy plate having various Ni concentration gradients in the surface layer.
[0074] Each copper alloy sheet was subjected to one of the following polishing treatments as a surface portion removal treatment. Physical polishing: Buff polishing Chemical polishing: Immersion in a polishing solution of sulfuric acid, hydrogen peroxide and polyoxyethylene dodecyl ether Electrolytic polishing: Pass electricity through a phosphoric acid solution using SUS304 as the counter electrode
[0075] As a comparative example, a copper alloy mother plate sample was also prepared that was not subjected to the Ni enrichment treatment and the surface removal treatment.
[0076] The Ni concentration at the surface and thickness direction of the copper alloy mother plate and each copper alloy plate was measured. The Ni concentration change in the thickness direction of each copper alloy plate was measured by the concentration profile in the depth direction by X-ray photoelectron spectroscopy (XPS). The measurement conditions for XPS are as follows.
[0077] (Measurement conditions) Pretreatment: Immerse in acetone solvent and pretreat using an ultrasonic cleaner at 38 kHz for 5 minutes. Equipment: ULVAC PHI X-ray photoelectron spectrometer PHI5000 VersaProbe Sputtering rate: 100Å / min Sputtering time: 100 minutes
[0078] The depths in the above XPS measurements are SiO2 equivalent depths, so the SiO2 equivalent depths in the XPS depth direction concentration profiles were converted to actual depths by comparing them with data measured separately by TEM-EDX (Energy Dispersive X-ray Spectroscopy) from a cross-sectional direction.
[0079] The bulk Ni concentration of each copper alloy mother plate was obtained by taking a sample from the center of the thickness where the Ni concentration was stable, measuring the maximum and minimum values by inductively coupled plasma atomic emission spectrometry (ICP-AES), and taking the arithmetic mean. Note that here, the bulk Ni concentration of each copper alloy plate is considered to be the same as the bulk Ni concentration of each copper alloy mother plate.
[0080] Next, the procedure for producing the copper alloy sheets with a plating film will be described. First, each copper alloy sheet produced by the above procedure was subjected to treatments such as degreasing and pickling to remove dirt and natural oxide films, and then a Cu plating layer was formed under the Cu plating conditions shown in Table 1. Next, a Sn plating layer was formed on each of the Cu-plated samples and the copper alloy mother sheet not subjected to Cu plating under the Sn plating conditions shown in Table 2, and the copper alloy sheets on which these plating layers (two-layer plating layers of a Cu plating layer / Sn plating layer, or a Sn plating layer) were formed were subjected to a reflow treatment to produce copper alloy sheets with a plating film.
[0081] In the reflow treatment, the plating layer was heated to a temperature within a range of 230° C. to 330° C., and then cooled to a temperature of 60° C. or less.
[0082] Then, samples were cut out from each copper alloy sheet with a plating film, and the Ni concentration in the plating film was measured. The Ni concentration in the plating film was measured from the concentration profile in the depth direction from the plating film surface by XPS, as in the case of the copper alloy sheet described above.
[0083] In addition, for each sample of bare copper alloy plate (copper alloy plate having no plating film), the surface contact electrical resistance was measured, and for each sample of copper alloy plate with a plating film, the surface contact electrical resistance, the adhesion of the plating film, and the solder wettability of the plating film surface were measured.
[0084] The contact electrical resistance was measured in accordance with JIS-C-5402 for samples heated at 180℃ for 24 hours using a four-terminal contact resistance tester (Yamazaki Seiki Kenkyusho: CRS-113-AU) to measure the load change-contact electrical resistance from 0 to 50g using a sliding type (distance: 1mm), and the contact electrical resistance was evaluated at a load of 50g. Contact electrical resistance values less than 5mΩ were rated as A, those between 5mΩ and less than 10mΩ as B, and those 10mΩ or more as C.
[0085] The solder wettability was evaluated in accordance with the soldering test method (balance method) of JIS-C60068-2-69 using a 5200TN solder checker made by Rhesca Corporation under the following flux application and soldering conditions.
[0086] (Flux application) Flux: 25% rosin-ethanol Flux temperature: Room temperature (25℃) Flux depth: 8mm Flux immersion time: 5 seconds Drip-cutting method: Place the edge against filter paper for 5 seconds to remove flux, then fix it to the device and hold for 30 seconds.
[0087] (Soldering) Solder composition: Sn-3.0%Ag-0.5%Cu manufactured by Senju Metal Industry Co., Ltd. Solder temperature: 240℃ Solder immersion speed: 10±2.5mm / sec Solder immersion depth: 2mm Solder immersion time: 10 seconds
[0088] From the obtained load / time curve, the time from the start of immersion until the buoyancy due to surface tension became zero (i.e. the contact angle between the solder and the sample became 90°) was taken as the zero-cross time (seconds). Solder wettability was rated as A (good) when the zero-cross time was less than 2 seconds, B (fair) when it was 2 to 4 seconds, and C (poor) when it was 4 seconds or more.
[0089] The adhesion of the plating film was evaluated by a cross-cut test on a sample heated at 180°C for 24 hours. The sample was cut with a utility knife to create 100 1mm square grids, and then cellophane tape (Nichiban Co., Ltd. #405) was pressed against the grids with finger pressure. After the cellophane tape was peeled off, if the plating film did not peel off, it was rated A, if three or fewer grids peeled off, it was rated B, and if four or more grids peeled off, it was rated C.
[0090] Tables 4 and 5 show the evaluation results for each of the bare material (copper alloy sheet) samples, and Tables 6 and 7 show the evaluation results for each of the plated copper alloy sheet samples.
[0091] In both tables, bulk Ni concentration is the Ni concentration (mass %) at the center of the thickness, surface Ni concentration is the Ni concentration at the surface of the copper alloy sheet at the stage where surface removal treatment has been performed and the unit is mass %, concentration ratio to bulk is the ratio of surface Ni concentration to bulk Ni concentration and the unit is %, surface layer thickness is the thickness from the surface of the copper alloy sheet to the point where the Ni concentration first reaches 90% of the bulk Ni concentration and the unit is μm, and concentration gradient is the gradient of Ni concentration in the surface layer and the unit is mass % / μm.
[0092] The surface layer thickness and concentration gradient are calculated from the depth direction concentration profile of the Ni component by XPS. Figure 2 shows an example of such a profile, which is for a sample in Example 1 in Table 4 with a bulk Ni concentration of 2.0 mass% and a concentration gradient of 19 mass% / μm. The concentration gradient refers to the gradient of the line connecting the surface Ni concentration point and the point in the profile where the bulk Ni concentration first reaches 90%.
[0093] In other words, if the change in Ni concentration in the depth direction profile from the plate surface to the point where the Ni concentration first reaches 90% of the bulk Ni concentration can be regarded as a straight line of roughly constant gradient, even with local fluctuations, the gradient of that profile is defined as the concentration gradient.
[0094] In Tables 6 to 7, the unit of the thickness of the Cu plating layer is μm, and the thickness of the Cu plating layer is "0" means that only the Sn plating process was performed without the Cu plating process. The thickness of the Sn plating layer was 1.0 μm in all samples shown in Tables 6 to 7.
[0095] [Table 3]
[0096] [Table 4]
[0097] [Table 5]
[0098] [Table 6]
[0099] [Table 7]
[0100] For the bare copper alloy sheets shown in Tables 4 and 5, in the examples in Table 4, those (Examples 5, 7, 10, and 14) with a relatively high surface Ni concentration (ratio to bulk concentration) had a contact resistance of B, which was higher than the other examples (contact resistance A). In addition, in the comparative examples in Table 5, all of Comparative Examples 1 to 5, in which the ratio to bulk concentration exceeded 70%, had a contact resistance of C. In Comparative Example 6, although the ratio to bulk concentration was smaller than 70%, the Ni concentration gradient exceeded 100 mass % / μm, which is thought to have caused the connection electrical resistance after heating to increase, resulting in a C.
[0101] In addition, in the copper alloy sheets with plating film shown in Tables 6 to 7, in the examples in Table 6, the Ni concentration gradient was large (Examples 6, 11, and 13), and the surface Ni concentration to bulk concentration ratio was large (Examples 5, 7, 10, and 14), either of the evaluation results was B. This tendency was particularly noticeable in the samples in which only Sn plating was performed without Cu plating (0 μm) when the plating layer was formed. As for the comparative examples in Table 7, Comparative Examples 1 and 5, which were not subjected to Ni enrichment treatment and surface removal treatment ("concentration gradient" is "∞ (untreated)"), and Comparative Examples 3 and 4, which had a high bulk Ni concentration and a bulk concentration ratio significantly exceeding 70%, all had poor contact resistance, plating adhesion, and solder wettability. As for Comparative Examples 2 and 6, the contact resistance and solder wettability were better than the others in the case of the Cu plating of 1.0 μm, but the bulk concentration ratio of Comparative Example 2 and the Ni concentration gradient of Comparative Example 6 were both beyond the range of the present invention, so that the adhesion was poor even when a plating film was formed.
[0102] [Example 2] Each copper alloy sheet having various Ni concentration gradients was prepared from a copper alloy mother sheet having a bulk Ni concentration of 2.0 mass% and a Si concentration of 0.4 mass% in the same manner as in Example 1, and then each copper alloy sheet was plated in the same manner as in Example 1 to prepare each copper alloy sheet with a plating film, and the Ni concentration in the Sn plating layer of each copper alloy sheet with a plating film was measured by XPS under the same conditions as in Example 1. Then, the ratio of the Ni concentration in the Sn plating layer to the bulk Ni concentration (relative to bulk concentration ratio) and solder wettability of each copper alloy sheet with a plating film were confirmed. The results are shown in Table 8.
[0103] [Table 8]
[0104] As shown in Table 8, in the sample (Comparative Example 7) in which the Ni concentration gradient exceeded 100 mass % / μm, the Ni concentration in the Sn plating layer exceeded 10% in terms of the bulk concentration ratio, and the solder wettability deteriorated.
[0105] [Example 3] A sample with a Ni concentration gradient of 25 mass% / μm was prepared from a copper alloy mother plate with a bulk Ni concentration of 2.0 mass% and a Si concentration of 0.4 mass% in the same manner as in Example 1. In preparation, the amount of surface removal in the surface removal treatment was varied to obtain copper alloy plates with the same concentration gradient but different surface Ni concentrations. The prepared copper alloy plate was plated in the same manner as in Example 1 to prepare a copper alloy plate with a plating film, and the plating adhesion and solder wettability of the copper alloy plate with a plating film were measured. The results are shown in Table 9. In Table 9, the "concentration ratio to bulk" is the ratio of the surface Ni concentration to the bulk Ni concentration in the copper alloy plate, as in Example 1.
[0106] [Table 9]
[0107] As shown in Table 9, in the sample (Comparative Example 8) in which the bulk concentration ratio exceeded 70%, the contact electrical resistance, plating adhesion, and solder wettability after heating deteriorated.
[0108] [Example 4] In the same manner as in Example 1, copper alloy sheets (bare materials) were prepared with a bulk Ni concentration of 2.0 mass% and a Si concentration of 0.4 mass% in the copper alloy sheet, various Ni concentration gradients in the surface layer, and the surface Ni concentration adjusted to 0 mass%, and then only one layer of various metal plating layers was formed. In this example, only plating was performed, and reflow was not performed. The metal species of the plating layers were Sn, Cu, Zn, Au, Ag, and Pd. The plating current density was 3 A / dm 2 The thickness of the plating film was 1 μm. The plating baths may be any of the commonly used acidic, neutral, and alkaline baths. In this example, an acidic bath was used for Sn, Cu, Zn, and Pd, and an alkaline bath was used for Au and Ag.
[0109] The contact resistance, solder wettability, and plating film adhesion of the samples prepared by the above procedure after heating were evaluated. The evaluation and judgment methods were the same as those in Example 1. The evaluation results are shown in Tables 10 and 11.
[0110] [Table 10]
[0111] [Table 11]
[0112] As shown in Tables 10 and 11, the solder wettability was good in both the examples shown in Table 10 and the comparative examples shown in Table 11. However, as shown in the comparative example in Table 11, in the sample in which the Ni concentration gradient exceeded 100 mass% / μm, peeling of the plating film occurred after heating.
[0113] Although the above examples include a plating film consisting of only one plating layer (Sn plating layer), a plating film structure consisting of multiple plating layers may be used. Furthermore, various metals may be alloyed by a process such as heating in order to reduce costs and further improve characteristics.
[0114] For example, in the case of a combination of a Cu plating layer and a pure Sn plating layer, if reflow processing cannot be performed due to some characteristic reasons, an unintended alloy layer may be formed over time between the pure tin plating layer and the underlying copper (copper alloy sheet or Cu plating layer). Since whiskers may be generated due to factors such as internal plating stress caused by the alloy layer, the Sn plating layer may be made into an alloy plating layer of Sn and Cu or Ag to suppress whiskers. [Industrial Applicability]
[0115] In a Cu-Ni-Si-based copper alloy sheet, the oxidation of the sheet surface can be suppressed and the electrical connection reliability can be improved. When a plating film is provided, the electrical connection reliability of the plating film surface, the adhesion between the plating film and the copper alloy sheet, and the solder wettability of the plating film surface can be improved. [Explanation of symbols]
[0116] 1. Cu-Ni-Si based copper alloy plate with plating film 10 Copper alloy plate (Cu-Ni-Si copper alloy plate) 10a plate surface 11 Surface layer 12 Inside the board 20 Plating film 20a Plating film surface 21 Cu layer 22 Sn-Cu alloy layer 23 Sn layer
Claims
1. A Cu-Ni-Si based copper alloy sheet, comprising at a thickness center portion in a thickness direction thereof 0.4% by mass or more and 5.0% by mass or less of Ni and 0.05% by mass or more and 1.2% by mass or less of Si, with the remainder being Cu and unavoidable impurities, characterized in that a surface Ni concentration at the sheet surface is 70% or less of the Ni concentration at the thickness center portion, and in a surface layer portion at a depth from the sheet surface to a depth at which the Ni concentration is 90% of the Ni concentration at the thickness center portion, the Ni concentration increases with a concentration gradient of 5% by mass / μm or more and 100% by mass / μm or less from the sheet surface toward the thickness center portion.
2. The Cu-Ni-Si based copper alloy sheet according to claim 1, characterized in that the thickness of the surface layer is 0.8 μm or less.
3. The Cu-Ni-Si-based copper alloy sheet according to claim 1 or 2, further comprising one or more of 0.1 mass% or more and 1.0 mass% or less of Co, 0.1 mass% or more and 1.0 mass% or less of Sn, and 0.1 mass% or more and 3.0 mass% or less of Zn.
4. The Cu-Ni-Si based copper alloy sheet according to any one of claims 1 to 3, further comprising 0.001 mass% or more and 0.2 mass% or less of Mg.
5. The Cu-Ni-Si-based copper alloy sheet according to any one of claims 1 to 4, further comprising one or more of 0.007% by mass or more and 0.25% by mass or less of Fe, 0.001% by mass or more and 0.2% by mass or less of P, 0.0001% by mass or more and 0.001% by mass or less of C, 0.001% by mass or more and 0.3% by mass or less of Cr, and 0.001% by mass or more and 0.3% by mass or less of Zr.
6. A plated Cu-Ni-Si-based copper alloy plate according to any one of claims 1 to 5, characterized in that a plated film is formed on the surface layer of the Cu-Ni-Si-based copper alloy plate, the plated film being composed of a Cu layer having a thickness of 0 μm to 1 μm, a Sn-Cu alloy layer having a thickness of 0.1 μm to 1.5 μm, and a Sn layer having a thickness of 0.1 μm to 3.0 μm in this order.
7. A Cu-Ni-Si system copper alloy plate with a plating film, characterized in that a plating film consisting of one or more layers selected from tin, copper, zinc, gold, silver, palladium and alloys thereof is formed to a thickness of 1 μm or less on the surface layer of the Cu-Ni-Si system copper alloy plate described in any one of claims 1 to 5.
8. 8. The plated Cu-Ni-Si system copper alloy sheet according to claim 6, wherein an average concentration of Ni in the plated film is 10% or less of the Ni concentration in the thickness center portion.
9. A method for producing the Cu-Ni-Si-based copper alloy plate according to any one of claims 1 to 5, comprising: a Ni enrichment treatment for diffusing Ni in the Cu-Ni-Si-based copper alloy plate toward a surface of the Cu-Ni-Si-based copper alloy plate to generate a Ni concentration gradient in the plate thickness direction and form a surface portion enriched in Ni; and a surface portion removal treatment for removing the Ni enriched surface portion to form the surface layer portion.
10. A method for producing a Cu-Ni-Si-based copper alloy sheet having a plating film according to any one of claims 6 to 8, comprising the steps of: applying a current density of 0.1 A / dm 2 More than 60A / dm 2 A method for producing a Cu-Ni-Si based copper alloy sheet having a plating film, the method being characterized by forming the plated film by the following electrolytic plating treatment.
11. After the electrolytic plating process for forming the plating film containing tin, the heating peak temperature is 230° C.
11. The method for producing a Cu-Ni-Si based copper alloy sheet having a plating film according to claim 10, characterized in that the reflow treatment is performed at a peak heating temperature of 0.5 to 30 seconds, and the heating time at the peak heating temperature is from 0.5 to 30 seconds.
Citation Information
Patent Citations
Cu alloy for electric and electronic part excellent in hot workability and suitability to blanking
JP1994145847A
Cu-Ni-Si BASED COPPER ALLOY SHEET FOR Sn PLATING
JP2010111926A
Cu-Ni-Si-BASED COPPER ALLOY Sn PLATED SHEET AND MANUFACTURING METHOD THEREFOR
JP2014005481A
Cu-Ni-Si BASED COPPER ALLOY SHEET HAVING EXCELLENT SPRING CRITICAL VALUE AND STRESS RELAXATION RESISTANCE AND HAVING SATISFACTORY THERMAL PEELING RESISTANCE AFTER Sn PLATING
JP2014019910A
Tin-plated copper alloy terminal material excellent in withdrawal property
JP2014208878A
